The problems of educational field experience for the students of elementary school teacher education study programs during the pandemic - Setianti, Tiyas Puji; Hartati, Tatat (Research and Social Study Institute, 2023)
Change suddenly resulted in many educational institutions has not avoided congestion strategy, facilities, and infrastructure held distance learning or online learning. Limitations of media and the skill to operate the hardware and software as a means and infrastructures major can lead to learning that is done it becomes less efficient. Learning done online is rated less effective, so lowering the interaction between lecturers and students and the impact that the students felt, they are difficulty understanding the material and ask the material that they have yet to understand due to lack of concentration. This study will use the descriptive survey that seeks to explain or record the conditions that can describe the situation. In line with the research, objectives sought to describe the difficulties of the students of teacher training that is being or has been carried out in the course PPL SP in elementary schools when the pandemic COVID -19 takes place. The Data obtained will be analyzed using descriptive statistics. It is selected because it corresponds with the purpose of the descriptive method selected. Descriptive statistics serve to interpret the data more easily. Problems faced by students of PGSD Universitas Pendidikan Indonesia in the Campus Area of the Attack, among others, difficulties during the implementation of online learning that includes the process of opening and closing the lesson as well as delivering material to the students. Arouse students ' motivation was to be the task of the student PPL SP that difficult.